Penerapan metode RUP dalam pengembangan website booking pada Hotel Sriwidjaya Palembang - Siti Fatimah Az Zahrah; Veraldo Veraldo; Novan Wijaya (Universitas Multi Data Palembang, 2026)
The development of information technology encourages hotels to improve their reservation services through digital platforms. Hotel Sriwidjaya Palembang still applies a manual booking process that may cause data inaccuracies and inefficiencies in service delivery. This research aims to implement the RUP (Rational Unified Process) method in developing a web-based hotel booking website to support online reservations and reservation management. The research scope focuses on the system development stages consisting of Inception, Elaboration, Construction, and Transition. The website is developed with features such as room availability information, online booking, and reservation management. The result show that the implementation of the RUP method can produce a structured and functional hotel booking website that improves reservation accuracy and service efficiency. In conclusion, the developed website is expected to assist Hotel Sriwidjaya in managing reservations more effectively and providing better services to customers.